Pengaruh Pelayanan dan Fasilitas Terhadap Tingkat Kepuasan Pelanggan Pada Cordela Inn Millennium Hotel Medan - Parjo Sihite; Riandani Rezki Prana (CIVITAS: Jurnal Studi Manajemen, 2022)
This research aimed at analyzing the influence of service and facility on customer’s satisfaction at Cordela Inn Millennium Hotel Medan. This research belongs to quantitative research with variables of service, facility and customer’s satisfaction. The data were collected by means of questionnaire, interview, observation, and documentation. The accidental sampling technique were deployed to obtain 89 respondents of Cordela Inn Millennium Hotel Medan. The data were then analyzed using multiple linear regression formula. The result of determination coefficient showed score of R Square was 0.577%, that meant the influence of service and facility on customer’s satisfaction was 57.7%. From the result of this research, it can be concluded that of service and facility variables have positive influence and significant on customer’s satisfaction at Cordela Inn Millennium Hotel Medan.